2022
DOI: 10.7717/peerj.13833
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorated sleep quality and influencing factors among undergraduates in northern Guizhou, China

Abstract: Background The sleep quality of undergraduates is considerably worse than that in general population, a cross sectional study was conducted to evaluate sleep quality and identify related factors. Methods All participants from the freshmen to senior were recruited by the stratified cluster sampling from December 1, 2018 to January 12, 2019. The questionnaire used in this research was primarily composed of three sections: demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Meanwhile, the incidence of sleep disorders in undergraduate student population is high due to their poor lifestyle habits ( Falavigna et al, 2011 ). A survey in Guizhou, China, showed that about 53.7% of college students experienced poor sleep ( Zhou et al, 2022 ). Sleep disorders among undergraduates have become a common and prominent harmful public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the incidence of sleep disorders in undergraduate student population is high due to their poor lifestyle habits ( Falavigna et al, 2011 ). A survey in Guizhou, China, showed that about 53.7% of college students experienced poor sleep ( Zhou et al, 2022 ). Sleep disorders among undergraduates have become a common and prominent harmful public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, newer models of cell phones currently have the ability to turn off blue light, and this study did not investigate the condition with blue light turned off, so this finding may have limitations. A gender-specific study (Zhou et al, 2022 ) found that smoking was a risk factor for poor sleep quality among males, and noisy dormitory and academic pressure were risk factors for poor sleep quality among females. A study on college students of Jilin Province (Li Y. et al, 2020 ) found that drinking, academic pressure, and relationships with classmates were risk factors for poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a significant number of undergraduates are experiencing poor sleep quality. In some provinces of China, the proportion of undergraduates with poor sleep quality has crossed more than 30.0%; for example, the proportions in Jilin, Guizhou, and Hong Kong were 33.8%, 53.7%, and 57.5%, respectively (Suen et al, 2008 ; Li Y. et al, 2020 ; Zhou et al, 2022 ). Sleep quality among undergraduate students has also been poor in other countries such as Ethiopia (57.5%) and India (51.0%) (Lemma et al, 2012 ; Ghrouz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep quality can cause physiological and psychological changes in college students, and they are easy to lead to related diseases in the long run.The literature reported that there were close associations between poor sleep status and illness, including hypertension 6 , diabetes 7 and so on 8 .Accumulating evidence shows that poor sleep status is also related to mental health,especially anxiety 9 and depression 10 .The profound in uence of sleep disorders on college students has attracted wide attention from students themselves and the society.Existing studies have reported that there are various factors can affect the sleep quality of college students,including individual characteristics,behavioral and lifestyle factors and physical and mental health factors [11][12][13] . Thus, by investigating the sleep status of college students and analyzing the in uencing factors, we can provide feasible intervention measures to promote the physical and mental health of college students.…”
Section: Introductionmentioning
confidence: 99%